Difference between revisions of "2016 AMC 12A Problems/Problem 12"

(Added another solution, using only the Angle Bisector Theorem)
Line 28: Line 28:
  
 
== Solution 3 ==
 
== Solution 3 ==
We denote CD by <math>y</math> and DB by <math>x</math>. Then, with the Angle Bisector Theorem in triangle ACB with angle bisector AD, we have  
+
We denote <math>CD</math> by <math>y</math> and <math>DB</math> by <math>x</math>. Then, with the Angle Bisector Theorem in triangle <math>ACB</math> with angle bisector <math>AD</math>, we have  
 
<math>\frac{x}{6}=\frac{y}{8}</math> or <math>y=\frac{4x}{3}.</math> However, <math>x+y=7,</math> so <math>x+\frac{4x}{3}=7</math> or <math>x=3.</math>  
 
<math>\frac{x}{6}=\frac{y}{8}</math> or <math>y=\frac{4x}{3}.</math> However, <math>x+y=7,</math> so <math>x+\frac{4x}{3}=7</math> or <math>x=3.</math>  
Now, we use the Angle Bisector Theorem again in triangle ADB with angle bisector BF. We get
+
Now, we use the Angle Bisector Theorem again in triangle <math>ADB</math> with angle bisector <math>BF.</math> We get
 
<math>\frac{AF}{6}=\frac{FD}{3}</math> or  
 
<math>\frac{AF}{6}=\frac{FD}{3}</math> or  
 
<math>\frac{AF}{FD}=\frac{2}{1},</math> which gives us the answer <math>\frac{AF}{AD} =\boxed{\textbf{(C)}\; 2 : 1}</math>
 
<math>\frac{AF}{FD}=\frac{2}{1},</math> which gives us the answer <math>\frac{AF}{AD} =\boxed{\textbf{(C)}\; 2 : 1}</math>

Revision as of 20:57, 9 February 2016

Problem 12

In $\triangle ABC$, $AB = 6$, $BC = 7$, and $CA = 8$. Point $D$ lies on $\overline{BC}$, and $\overline{AD}$ bisects $\angle BAC$. Point $E$ lies on $\overline{AC}$, and $\overline{BE}$ bisects $\angle ABC$. The bisectors intersect at $F$. What is the ratio $AF$ : $FD$?

[asy] pair A = (0,0), B=(6,0), C=intersectionpoints(Circle(A,8),Circle(B,7))[0], F=incenter(A,B,C), D=extension(A,F,B,C),E=extension(B,F,A,C); draw(A--B--C--A--D^^B--E); label("$A$",A,SW); label("$B$",B,SE); label("$C$",C,N); label("$D$",D,NE); label("$E$",E,NW); label("$F$",F,1.5*N); [/asy]

$\textbf{(A)}\ 3:2\qquad\textbf{(B)}\ 5:3\qquad\textbf{(C)}\ 2:1\qquad\textbf{(D)}\ 7:3\qquad\textbf{(E)}\ 5:2$

Solution

By the angle bisector theorem, $\frac{AB}{AE} = \frac{CB}{CE}$

$\frac{6}{AE} = \frac{7}{8 - AE}$ so $AE = \frac{48}{13}$

Similarly, $CD = 4$.

Now, we use mass points. Assign point $C$ a mass of $1$.

$mC \cdot CD = mB \cdot DB$ , so $mB = \frac{4}{3}$

Similarly, $A$ will have a mass of $\frac{7}{6}$

$mD = mC + mB = 1 + \frac{4}{3} = \frac{7}{3}$

So $\frac{AF}{AD} = \frac{mD}{mA} = \boxed{\textbf{(C)}\; 2 : 1}$

Solution 2

Denote $[\triangle{ABC}]$ as the area of triangle ABC and let $r$ be the inradius. Also, as above, use the angle bisector theorem to find that $BD = 3$. Note that $F$ is the incenter. Then, $\frac{AF}{FD} = \frac{[\triangle{AFB}]}{[\triangle{BFD}]} = \frac{AB * \frac{r}{2}}{BD * \frac{r}{2}} = \frac{AB}{BD} =  \boxed{\textbf{(C)}\; 2 : 1}$

Solution 3

We denote $CD$ by $y$ and $DB$ by $x$. Then, with the Angle Bisector Theorem in triangle $ACB$ with angle bisector $AD$, we have $\frac{x}{6}=\frac{y}{8}$ or $y=\frac{4x}{3}.$ However, $x+y=7,$ so $x+\frac{4x}{3}=7$ or $x=3.$ Now, we use the Angle Bisector Theorem again in triangle $ADB$ with angle bisector $BF.$ We get $\frac{AF}{6}=\frac{FD}{3}$ or $\frac{AF}{FD}=\frac{2}{1},$ which gives us the answer $\frac{AF}{AD} =\boxed{\textbf{(C)}\; 2 : 1}$

See Also

2016 AMC 12A (ProblemsAnswer KeyResources)
Preceded by
Problem 11
Followed by
Problem 13
1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25
All AMC 12 Problems and Solutions

The problems on this page are copyrighted by the Mathematical Association of America's American Mathematics Competitions. AMC logo.png

Invalid username
Login to AoPS